Simultaneous pancreas-kidney transplantation after liver transplantation: first Portuguese case report - Soares,Elsa (2020)
Simultaneous kidney pancreas transplantation, if feasible, is the treatment of choice for the management of end-stage renal disease in patients with type 1 diabetes. This intervention can offer glycemic control and might also stabilize or even reverse some of the metabolic complications of diabetes. Chronic kidney disease has become a critical problem in orthotopic liver transplantation due to multiple risk factors, including post-transplant diabetes mellitus and immunosuppression. This has a major impact on graft and patient survival. In this paper we present the case of a 42-year-old man submitted to a simultaneous pancreas kidney transplant after a successful liver transplantation 18 years earlier. The surgical procedure was uneventful, and the patient was discharged 18 days after admission. The case findings support that simultaneous pancreas and kidney transplantation is an effective method for the treatment of chronic kidney disease in patients with diabetes and a previous liver transplant.